Rice husk-based silicon-carbon composite material for lithium ion battery negative electrode and preparation method thereof

CN122800595APending Publication Date: 2026-09-22SHENGZHOU SIGMA TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611248606.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0003]其中单质硅理论比容量约4200mAh/g,氧化亚硅可达2600mAh/g,应用潜力巨大,但硅基材料存在致命缺陷,充放电过程中体积膨胀率超300%,极易引发电极粉化、固体电解质界面膜反复破裂与再生,最终导致电池容量快速衰减、循环性能大幅下降,严重制约其产业化应用

Benefits of technology

1、本发明提供熔盐辅助镁热还原与催化碳热还原两条制备路径,均可将稻壳中天然赋存的二氧化硅高效还原为活性硅组分,并均匀分散于生物质碳基体中;其中熔盐介质可强化反应传质效率,铁基催化体系可降低还原反应活化能,均能实现硅组分的深度还原,使制得的硅碳复合材料具备较高的首次充放电比容量与首次库伦效率,同时展现出优异的长循环容量保持能力,可充分适配高能量密度锂离子电池的负极性能需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800595A_ABST
    Figure CN122800595A_ABST
Patent Text Reader

Abstract

The application discloses a rice hull-based silicon-carbon composite material for a lithium ion battery negative electrode and a preparation method thereof, and belongs to the technical field of lithium ion battery negative electrode materials. Dry rice hulls are soaked in hydrochloric acid, filtered and washed, dried and ball milled to obtain pretreated rice hull powder; and a silicon-carbon composite material is prepared by a molten salt assisted magnesium thermal reduction method or a catalytic carbon thermal reduction method. The application provides two preparation paths of the molten salt assisted magnesium thermal reduction and the catalytic carbon thermal reduction, and the two paths can efficiently reduce the naturally-occurring silicon dioxide in the rice hulls into active silicon components. The prepared silicon-carbon composite material has high initial charge-discharge specific capacity and initial coulombic efficiency, and simultaneously exhibits excellent long cycle capacity retention capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery anode material technology, specifically to a rice husk-based silicon-carbon composite material for lithium-ion battery anodes and its preparation method. Background Technology

[0002] As lithium-ion batteries rapidly develop towards higher energy density, silicon-based materials such as elemental silicon and silicon suboxide have become core candidate materials for the next generation of high-performance lithium battery anodes due to their theoretical specific capacity far exceeding that of traditional carbon-based anodes.

[0003] Among them, elemental silicon has a theoretical specific capacity of about 4200 mAh / g, while silicon suboxide can reach 2600 mAh / g, showing great application potential. However, silicon-based materials have fatal defects. During charging and discharging, the volume expansion rate exceeds 300%, which can easily lead to electrode pulverization, repeated rupture and regeneration of the solid electrolyte interface film, ultimately resulting in rapid capacity decay and a significant decrease in cycle performance, which seriously restricts their industrial application.

[0004] Currently, the industry generally adopts silicon-carbon composite technology to improve the above problems. It uses carbon matrix to buffer the volume deformation of silicon-based materials, improve the conductivity of electrodes and stabilize the interface structure. Existing commercial silicon suboxide / carbon composite materials are mainly prepared by mechanical mixing, chemical vapor deposition and sol-gel method, which generally have problems such as uneven distribution of silicon and carbon phases and weak interfacial bonding strength.

[0005] Rice husks, as an abundant agricultural waste, are rich in silica and organic matter and have a natural porous structure, making them an excellent precursor for the preparation of silicon-carbon composite materials. However, the traditional preparation process of rice husk-based silicon-carbon materials is cumbersome and lacks an efficient composite process, making it difficult to achieve uniform composite of silicon-based nano-components in a carbon matrix. This limits the large-scale preparation and application of low-cost, high-performance silicon-carbon anode materials.

[0006] Based on this, the present invention designs a rice husk-based silicon-carbon composite material for lithium-ion battery anodes and its preparation method to solve the above problems. Summary of the Invention

[0007] To address the aforementioned shortcomings of existing technologies, this invention provides a method for preparing rice husk-based silicon-carbon composite materials for lithium-ion battery anodes, comprising the following steps: S1: Soak dried rice husks in hydrochloric acid solution, filter and wash after soaking, dry and ball mill to obtain pretreated rice husk powder; S2: Silicon-carbon composite materials are prepared by pretreated rice husk powder through molten salt-assisted magnesothermic reduction or catalytic carbothermic reduction. S3: Mix silicon-carbon composite material, conductive carbon black and binder to obtain a mixture, add deionized water and disperse to make electrode slurry; coat the electrode slurry onto copper foil current collector, and after drying, rolling and cutting, obtain rice husk-based silicon-carbon composite material for lithium-ion battery negative electrode.

[0008] Furthermore, the molten salt-assisted magnesium thermal reduction method specifically includes the following steps: A1. Pretreated rice husk powder is heated to 400-500℃ at 3-8℃ / min under a nitrogen atmosphere and kept at that temperature for 1-3h. It is then naturally cooled to room temperature to obtain rice husk carbon precursor. A2. Mix rice husk carbon precursor, magnesium powder (325 mesh) and NaCl-KCl eutectic molten salt at a molar ratio of silicon dioxide, magnesium powder and molten salt of 1:1.5-2.5:0.8-1.1 at 300-400 r / min for 10-30 min. A3. Load the mixture into an alumina crucible and transfer it into a tube furnace. Heat the furnace to 700-900℃ and hold for 2-6 hours. After the reaction is complete, allow it to cool naturally to room temperature. A4. Grind the cooled product to a particle size of 1-10 μm, immerse it in a 3 mol / L hydrochloric acid solution with a solid-liquid ratio of 1:10-20 g / mL, and stir at room temperature for 10-15 h. After filtration, wash with deionized water until the pH of the filtrate is 6.5-7.5. Then transfer the product to a 1-2 g / L dopamine Tris buffer solution (pH=8.5), stir at room temperature for 4-8 h for in-situ coating, and then dry at 70-90℃ for 10-18 h to obtain a silicon-carbon composite material.

[0009] Furthermore, the preparation method of the NaCl-KCl eutectic molten salt is as follows: Analytical grade NaCl and KCl in a molar ratio of 2.5-3.0:1 are first dried at 200℃ for 72 hours to initially remove adsorbed moisture; after mixing, they are placed in a corundum / alumina crucible, placed in a high-temperature resistance furnace, and then heated to 300℃ and held for 10 hours to further remove moisture. The dehydrated and mixed salt is then heated to 660-700℃ and held until the salt is completely melted into a homogeneous liquid phase, thus obtaining the NaCl-KCl eutectic molten salt.

[0010] Furthermore, the catalytic carbothermic reduction method specifically includes the following steps: B1. Place the pretreated rice husk powder and iron citrate catalyst (iron element mass accounts for 1-3% of the total powder mass) in a ball mill and ball mill at a speed of 400-600 r / min for 1-4 h to obtain refined rice husk powder. B2. The refined rice husk powder is heated to 700-800℃ at 4-6℃ / min under an inert atmosphere and kept at that temperature for 4-8h. After the reaction is completed, it is naturally cooled to room temperature. B3. Wash the cooled product repeatedly with deionized water, and then dry it at 70-90℃ for 10-24h to obtain the silicon-carbon composite material.

[0011] Furthermore, S1 specifically involves taking 80-120 parts by weight of rice husks, washing them with deionized water for 15-30 minutes, and then drying the washed rice husks at 60-100℃ for 6-18 hours to obtain dried rice husks. Soak dried rice husks in a 2 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:8-15 g / mL for 12-24 hours at room temperature, stirring once every 2-4 hours during the soaking period. After soaking, filter the cake and wash it with deionized water until the pH of the filtrate is neutral. Then dry it at 70-100℃ for 8-12 hours and then transfer it to a planetary ball mill and dry ball mill at 200-300r / min for 30-60 minutes to obtain pretreated rice husk powder.

[0012] Furthermore, S3 specifically involves mixing silicon-carbon composite material, conductive carbon black Super P, and binder LA136D at a mass ratio of 6-8:1-2:1-1.5 to obtain a mixture. Then, deionized water with a mass of 0.8-1.5 times the total mass of the mixture is added. The mixture is first pre-dispersed at a low speed of 500-800 r / min for 1-2 h, and then stirred at a high speed of 1000-2000 r / min for 2-6 h to prepare an electrode slurry. Electrode slurry is coated onto copper foil current collector with a coating thickness of 50-150 μm and dried at 80-120℃ for 12-24 h. After rolling and cutting, it is heat-treated in a vacuum environment at 60℃ for 2-4 h to remove residual solvent and internal stress, thus obtaining rice husk-based silicon-carbon composite material for lithium-ion battery anodes.

[0013] A rice husk-based silicon-carbon composite material for lithium-ion battery anodes prepared according to the method.

[0014] Compared with the prior art, the beneficial effects of this invention are as follows: 1. This invention provides two preparation routes: molten salt-assisted magnesium thermal reduction and catalytic carbothermic reduction. Both routes can efficiently reduce the naturally occurring silicon dioxide in rice husks into active silicon components, which are then uniformly dispersed in the biomass carbon matrix. The molten salt medium can enhance the reaction mass transfer efficiency, and the iron-based catalytic system can reduce the activation energy of the reduction reaction. Both routes can achieve deep reduction of the silicon components, resulting in silicon-carbon composite materials with high initial charge-discharge specific capacity and initial coulombic efficiency. At the same time, they exhibit excellent long-cycle capacity retention capabilities, which can fully meet the anode performance requirements of high-energy-density lithium-ion batteries.

[0015] 2. This invention uses rice husks, a major agricultural waste, as the core precursor. It makes full use of the natural characteristics of rice husks, which are enriched with both silicon components and organic matter. It can achieve in-situ preparation of silicon-carbon composite materials without the need to add complex silicon and carbon sources. This can realize the high-value conversion of biomass waste, while simplifying the material preparation process. It has good adaptability to large-scale production and broad application prospects. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0017] Figure 1 This is a scanning electron microscope image of the silicon-carbon composite material prepared in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the silicon-carbon composite material obtained in Example 2 of the present invention; Figure 3 These are the initial charge-discharge performance test diagrams for embodiments and comparative examples of the present invention; Figure 4 The diagram shows the cyclic performance test results of embodiments and comparative examples of the present invention. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0019] Example 1: This example provides a method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery anodes, including the following steps: S1: Take 120 parts by weight of rice husks, wash them with deionized water for 30 minutes, and dry the washed rice husks at 100℃ for 18 hours to obtain dried rice husks. The dried rice husks were immersed in a 2 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:15 g / mL for 24 hours at room temperature, and stirred once every 4 hours during the soaking period. After soaking, filter the cake and wash it with deionized water until the pH of the filtrate is neutral. Then dry it at 100℃ for 12 hours and then transfer it to a planetary ball mill and dry ball mill at 300r / min for 60 minutes to obtain pretreated rice husk powder. S2: Pretreated rice husk powder was placed in a tube furnace and subjected to high-temperature treatment under inert gas protection. Silicon-carbon composite material was prepared by molten salt-assisted magnesiothermal reduction (its electron micrograph is shown below). Figure 1 (as shown) S3: Mix silicon-carbon composite material, conductive carbon black Super P and binder LA136D at a mass ratio of 8:2:1.5 to obtain a mixture. Add deionized water at a mass of 1.5 times the total mass of the mixture. First, pre-disperse at a low speed of 800 r / min for 2 h, and then stir at a high speed of 2000 r / min for 6 h to prepare electrode slurry. Electrode slurry was coated onto a copper foil current collector with a coating thickness of 50 μm. After drying at 120°C for 24 h, it was rolled and cut, and then heat-treated in a vacuum environment at 60°C for 4 h to remove residual solvent and internal stress, thus obtaining rice husk-based silicon-carbon composite material for lithium-ion battery anodes.

[0020] The molten salt-assisted magnesium thermal reduction method specifically includes the following steps: A1. The pretreated rice husk powder was heated to 500℃ at 8℃ / min under a nitrogen atmosphere and kept at that temperature for 3h. It was then naturally cooled to room temperature to obtain the rice husk carbon precursor. A2. Mix rice husk carbon precursor, magnesium powder (325 mesh) and NaCl-KCl eutectic molten salt at a molar ratio of silicon dioxide, magnesium powder and molten salt of 1:2.5:1.1 at 400 r / min for 30 min. The preparation method of the NaCl-KCl eutectic molten salt is as follows: Analytical grade NaCl and KCl with a molar ratio of 3.0:1 are first dried at 200℃ for 72h to initially remove adsorbed moisture; after mixing, they are placed in a corundum / alumina crucible, placed in a high-temperature resistance furnace, and then heated to 300℃ and held for 10h to further remove moisture. The dehydrated and mixed salt is then heated to 700℃ and held until the salt is completely melted into a homogeneous liquid phase, thus obtaining the NaCl-KCl eutectic molten salt. The calculation procedure for determining silicon dioxide in rice husk carbon precursor is as follows: First, a certain mass of rice husk carbon precursor sample is sampled and weighed, then placed in a muffle furnace and completely ashed at 700℃. The ash is heated and boiled with sodium hydroxide solution to dissolve the silicon dioxide in the ash. Insoluble impurities are separated by filtration, resulting in a filtrate containing sodium silicate. Hydrated silicon dioxide is precipitated from the filtrate by acid precipitation. After filtration, washing, and drying, the dry weight of the precipitated silicon dioxide is weighed, and the final measured mass percentage of silicon dioxide is 86% ± 1.8%.

[0021] A3. Load the mixture into an alumina crucible and transfer it into a tube furnace. Heat the furnace to 900°C and hold for 6 hours. After the reaction is complete, allow it to cool naturally to room temperature. A4. Grind the cooled product to a particle size of 1-10 μm, immerse it in a 3 mol / L hydrochloric acid solution with a solid-liquid ratio of 1:20 g / mL, and stir at room temperature for 15 h; after filtration, wash with deionized water until the pH of the filtrate is 6.5-7.5, then transfer the product to a 2 g / L dopamine Tris buffer solution (pH=8.5), stir at room temperature for 8 h for in-situ coating, and then dry at 90℃ for 18 h to obtain a silicon-carbon composite material; Example 2: This example provides a method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery anodes, including the following steps: S1: Take 120 parts by weight of rice husks, wash them with deionized water for 30 minutes, and dry the washed rice husks at 100℃ for 18 hours to obtain dried rice husks. The dried rice husks were immersed in a 2 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:15 g / mL for 24 hours at room temperature, and stirred once every 4 hours during the soaking period. After soaking, filter the cake and wash it with deionized water until the pH of the filtrate is neutral. Then dry it at 100℃ for 12 hours and then transfer it to a planetary ball mill and dry ball mill at 300r / min for 60 minutes to obtain pretreated rice husk powder. S2: Pretreated rice husk powder was placed in a tube furnace and subjected to high-temperature treatment under inert gas protection to prepare silicon-carbon composite material via catalytic carbothermal reduction (its electron micrograph is shown in Figure 1). Figure 2 (as shown) S3: Mix silicon-carbon composite material, conductive carbon black Super P and binder LA136D at a mass ratio of 8:2:1.5 to obtain a mixture. Add deionized water at a mass of 1.5 times the total mass of the mixture. First, pre-disperse at a low speed of 800 r / min for 2 h, and then stir at a high speed of 2000 r / min for 6 h to prepare electrode slurry. Electrode slurry was coated onto a copper foil current collector with a coating thickness of 150 μm. After drying at 120 °C for 24 h, it was rolled and cut, and then heat-treated in a vacuum environment at 60 °C for 4 h to remove residual solvent and internal stress, thus obtaining rice husk-based silicon-carbon composite material for lithium-ion battery anodes.

[0022] The catalytic carbothermic reduction method specifically includes the following steps: B1. Place the pretreated rice husk powder and iron citrate catalyst (iron element mass accounts for 3% of the total powder mass) in a ball mill and ball mill at a speed of 600 r / min for 4 h to obtain refined rice husk powder; B2. The refined rice husk powder was heated to 800℃ at 6℃ / min under an inert atmosphere and kept at that temperature for 8 hours. After the reaction was completed, it was naturally cooled to room temperature. B3. The cooled product was repeatedly washed with deionized water and then dried at 90°C for 24 hours to obtain a silicon-carbon composite material.

[0023] Example 3: This example provides a method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery anodes, including the following steps: S1: Take 80 parts by weight of rice husks, wash them with deionized water for 15 minutes, and dry the washed rice husks at 60℃ for 6 hours to obtain dried rice husks. The dried rice husks were immersed in a 2 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:8 g / mL for 12 hours at room temperature, and stirred once every 2 hours during the soaking period. After soaking, filter the cake and wash it with deionized water until the pH of the filtrate is neutral. Then dry it at 70°C for 8 hours and then transfer it to a planetary ball mill and dry ball mill at 200 r / min for 30 min to obtain pretreated rice husk powder. S2: Pretreated rice husk powder is placed in a tube furnace and subjected to high-temperature treatment under inert gas protection. Silicon-carbon composite material is prepared by molten salt-assisted magnesia reduction method. S3: Mix silicon-carbon composite material, conductive carbon black Super P and binder LA136D at a mass ratio of 6:1:1 to obtain a mixture. Add deionized water at a mass of 0.8 times the total mass of the mixture. First, pre-disperse at a low speed of 500 r / min for 1 h, and then stir at a high speed of 1000 r / min for 2 h to prepare electrode slurry. Electrode slurry was coated onto a copper foil current collector with a coating thickness of 100 μm. After drying at 80 °C for 12 h, it was rolled and cut, and then heat-treated in a vacuum environment at 60 °C for 2 h to remove residual solvent and internal stress, thus obtaining rice husk-based silicon-carbon composite material for lithium-ion battery anodes.

[0024] The molten salt-assisted magnesium thermal reduction method specifically includes the following steps: A1. The pretreated rice husk powder was heated to 400℃ at 3℃ / min under a nitrogen atmosphere and kept at that temperature for 1h. It was then naturally cooled to room temperature to obtain the rice husk carbon precursor. A2. Mix rice husk carbon precursor, magnesium powder (325 mesh) and NaCl-KCl eutectic molten salt at 300 r / min for 10 min according to the molar ratio of silicon dioxide, magnesium powder and molten salt in the precursor of 1:1.5:0.8. The preparation method of the NaCl-KCl eutectic molten salt is as follows: Analytical grade NaCl and KCl with a molar ratio of 2.5:1 are first dried at 200℃ for 72h to initially remove adsorbed moisture; after mixing, they are placed in a corundum / alumina crucible, placed in a high-temperature resistance furnace, and then heated to 300℃ and held for 10h to further remove moisture. The dehydrated and mixed salt is then heated to 660℃ and held until the salt is completely melted into a homogeneous liquid phase, thus obtaining the NaCl-KCl eutectic molten salt. The calculation procedure for determining silicon dioxide in rice husk carbon precursor is as follows: First, a certain mass of rice husk carbon precursor sample is sampled and weighed, then placed in a muffle furnace and completely ashed at 700℃. The ash is heated and boiled with sodium hydroxide solution to dissolve the silicon dioxide in the ash. Insoluble impurities are separated by filtration, resulting in a filtrate containing sodium silicate. Hydrated silicon dioxide is precipitated from the filtrate by acid precipitation. After filtration, washing, and drying, the dry weight of the precipitated silicon dioxide is weighed, and the final measured mass percentage of silicon dioxide is 86% ± 1.8%.

[0025] A3. Load the mixture into an alumina crucible and transfer it into a tube furnace. Heat the furnace to 700°C and hold for 2 hours. After the reaction is complete, allow it to cool naturally to room temperature. A4. Grind the cooled product to a particle size of 1-10 μm, immerse it in a 3 mol / L hydrochloric acid solution with a solid-liquid ratio of 1:10 g / mL, and stir at room temperature for 10 h; after filtration, wash with deionized water until the pH of the filtrate is 6.5-7.5, then transfer the product to a 1 g / L dopamine Tris buffer solution (pH=8.5), stir at room temperature for 4 h for in-situ coating, and then dry at 70℃ for 10 h to obtain a silicon-carbon composite material; Example 4: This example provides a method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery anodes, including the following steps: S1: Take 80 parts by weight of rice husks, wash them with deionized water for 15 minutes, and dry the washed rice husks at 60℃ for 6 hours to obtain dried rice husks. The dried rice husks were immersed in a 2 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:8 g / mL for 12 hours at room temperature, and stirred once every 2 hours during the soaking period. After soaking, filter the cake and wash it with deionized water until the pH of the filtrate is neutral. Then dry it at 70°C for 8 hours and then transfer it to a planetary ball mill and dry ball mill at 200 r / min for 30 min to obtain pretreated rice husk powder. S2: Pretreated rice husk powder is placed in a tube furnace and subjected to high-temperature treatment under inert gas protection to prepare silicon-carbon composite material by catalytic carbothermal reduction. S3: Mix silicon-carbon composite material, conductive carbon black Super P and binder LA136D at a mass ratio of 6:1:1 to obtain a mixture. Add deionized water at a mass of 0.8 times the total mass of the mixture. First, pre-disperse at a low speed of 500 r / min for 1 h, and then stir at a high speed of 1000 r / min for 2 h to prepare electrode slurry. Electrode slurry was coated onto a copper foil current collector with a coating thickness of 100 μm. After drying at 80 °C for 12 h, it was rolled and cut, and then heat-treated in a vacuum environment at 60 °C for 2 h to remove residual solvent and internal stress, thus obtaining rice husk-based silicon-carbon composite material for lithium-ion battery anodes.

[0026] The catalytic carbothermic reduction method specifically includes the following steps: B1. Place the pretreated rice husk powder and iron citrate catalyst (iron element mass accounts for 1% of the total powder mass) in a ball mill and ball mill at a speed of 400 r / min for 1 h to obtain refined rice husk powder. B2. The refined rice husk powder was heated to 700℃ at 4℃ / min under an inert atmosphere and kept at that temperature for 4h. After the reaction was completed, it was naturally cooled to room temperature. B3. The cooled product was repeatedly washed with deionized water and then dried at 70°C for 10 hours to obtain a silicon-carbon composite material.

[0027] Comparative Example 1: The difference between this comparative example and Example 1 is that the NaCl-KCl eutectic molten salt component is removed in the molten salt-assisted magnesium thermal reduction step.

[0028] Comparative Example 2: The difference between this comparative example and Example 1 is that the in-situ coating process of dopamine Tris buffer solution was omitted in the post-magnesium reduction treatment step. After the product was soaked in hydrochloric acid and washed with deionized water until neutral, it was directly dried at 90°C for 18 hours to obtain silicon-carbon composite material. The subsequent electrode preparation steps were completely consistent with those in Example 1.

[0029] Comparative Example 3: The difference between this comparative example and Example 2 is that ferric citrate is replaced with ferric nitrate nonahydrate, while the mass of iron element still accounts for 3% of the total mass of the powder.

[0030] Experimental example: The first charge specific capacity (mAh / g), first discharge specific capacity (mAh / g), first coulombic efficiency (%), and capacity retention rate (%) of rice husk-based silicon-carbon composite materials for lithium-ion battery anodes prepared in each example and comparative example were tested according to GB / T 44027.1-2024.

[0031] The results are shown in the table below:

[0032] From the above table and Figure 3-4 It can be seen that Examples 1 and 3 using the molten salt-assisted magnesium thermal reduction process and Examples 2 and 4 using the catalytic carbothermic reduction process successfully prepared electrochemically active rice husk-based silicon-carbon anode materials. Examples 1 and 3 showed an initial charge specific capacity of 528-576 mAh / g, an initial discharge specific capacity of 937-986 mAh / g, an initial coulombic efficiency of 56.35-58.42%, and a capacity retention rate of 89.97-92.63% after 100 cycles. Examples 2 and 4 using the catalytic carbothermic reduction route showed an initial charge specific capacity of 361-415 mAh / g, an initial discharge specific capacity of 842-918 mAh / g, an initial coulombic efficiency of 42.87-45.21%, and a capacity retention rate of 80.05-81.78% after 100 cycles.

[0033] After removing the NaCl-KCl eutectic molten salt component from Comparative Example 1, the electrochemical performance of the material showed a significant decline compared to Example 1. The initial charge specific capacity decreased from 576 mAh / g to 309 mAh / g, the initial coulombic efficiency decreased from 58.42% to 37.64%, and the capacity retention after 100 cycles decreased from 92.63% to 87.62%. Without the molten salt medium, the magnesium thermal reduction can only occur through solid-gas contact. The limited contact area between magnesium and silicon dioxide in the rice husk carbon precursor and the low mass transfer efficiency lead to incomplete reduction reaction, an increased proportion of residual inert silicon dioxide, and a significant decrease in the content of active elemental silicon.

[0034] In Comparative Example 2, omitting the in-situ coating process with dopamine Tris buffer solution resulted in a comprehensive deterioration of the material's electrochemical performance. The initial charge specific capacity was only 263 mAh / g, the initial coulombic efficiency dropped to 34.97%, and the capacity retention rate after 100 cycles was only 72.61%. The carbon layer formed after polydopamine carbonization is the core for buffering silicon volume expansion and constructing a stable conductive network and interface. Without this coating layer, the nano-silicon particles lack mechanical constraint, and repeated volume expansion and contraction during charging and discharging easily lead to particle pulverization and detachment from the carbon matrix, causing deactivation of the active material.

[0035] In Comparative Example 3, after replacing the catalyst with ferric citrate and ferric nitrate nonahydrate with the same iron content, the material performance decreased significantly compared to Example 2. The initial charge specific capacity decreased from 415 mAh / g to 295 mAh / g, the initial coulombic efficiency decreased from 45.21% to 33.68%, and the capacity retention rate after 100 cycles decreased from 81.78% to 76.25%. This indicates that ferric citrate can achieve uniform dispersion of iron during ball milling and heating, forming highly active catalytic sites, effectively reducing the activation energy of carbothermic reduction, and promoting deep reduction of silica.

[0036] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a rice husk-based silicon-carbon composite material for lithium-ion battery anodes, characterized in that, Includes the following steps: S1: Soak dried rice husks in hydrochloric acid solution, filter and wash after soaking, dry and ball mill to obtain pretreated rice husk powder; S2: Silicon-carbon composite materials are prepared by pretreated rice husk powder through molten salt-assisted magnesothermic reduction or catalytic carbothermic reduction. S3: Mix silicon-carbon composite material, conductive carbon black and binder to obtain a mixture, add deionized water and disperse to make electrode slurry; coat the electrode slurry onto copper foil current collector, and after drying, rolling and cutting, obtain rice husk-based silicon-carbon composite material for lithium-ion battery negative electrode.

2. The method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery negative electrodes according to claim 1, characterized in that, The molten salt-assisted magnesium thermal reduction method specifically includes the following steps: A1. Pretreated rice husk powder is heated to 400-500℃ at 3-8℃ / min under a nitrogen atmosphere and kept at that temperature for 1-3h. It is then naturally cooled to room temperature to obtain rice husk carbon precursor. A2. Mix rice husk carbon precursor, magnesium powder and NaCl-KCl eutectic molten salt at a molar ratio of silicon dioxide, magnesium powder and molten salt of 1:1.5-2.5:0.8-1.1 at 300-400 r / min for 10-30 min. A3. Load the mixture into an alumina crucible and transfer it into a tube furnace. Heat the furnace to 700-900℃ and hold for 2-6 hours. After the reaction is complete, allow it to cool naturally to room temperature. A4. Grind the cooled product to a particle size of 1-10 μm, immerse it in a 3 mol / L hydrochloric acid solution with a solid-liquid ratio of 1:10-20 g / mL, and stir at room temperature for 10-15 h. After filtration, wash with deionized water until the pH of the filtrate is 6.5-7.

5. Then transfer the product to a 1-2 g / L dopamine Tris buffer solution and stir at room temperature for 4-8 h for in-situ coating. Finally, dry at 70-90℃ for 10-18 h to obtain the silicon-carbon composite material.

3. The method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery negative electrode according to claim 2, characterized in that, The preparation method of the NaCl-KCl eutectic molten salt is as follows: Analytical grade NaCl and KCl in a molar ratio of 2.5-3.0:1 are first dried at 200℃ for 72 hours to initially remove adsorbed moisture; after mixing, they are placed in a corundum / alumina crucible, placed in a high-temperature resistance furnace, and then heated to 300℃ and held for 10 hours to further remove moisture. The dehydrated and mixed salt is then heated to 660-700℃ and held until the salt is completely melted into a homogeneous liquid phase, thus obtaining the NaCl-KCl eutectic molten salt.

4. The method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery negative electrode according to claim 3, characterized in that, The catalytic carbothermic reduction method specifically includes the following steps: B1. Place the pretreated rice husk powder and iron citrate catalyst in a ball mill and ball mill at a speed of 400-600 r / min for 1-4 h to obtain refined rice husk powder; B2. The refined rice husk powder is heated to 700-800℃ at 4-6℃ / min under an inert atmosphere and kept at that temperature for 4-8h. After the reaction is completed, it is naturally cooled to room temperature. B3. Wash the cooled product repeatedly with deionized water, and then dry it at 70-90℃ for 10-24h to obtain the silicon-carbon composite material.

5. The method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery negative electrode according to claim 4, characterized in that, S1 is specifically: Take 80-120 parts by weight of rice husks, wash them with deionized water for 15-30 minutes, and dry the washed rice husks at 60-100℃ for 6-18 hours to obtain dried rice husks. Soak dried rice husks in a 2 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:8-15 g / mL for 12-24 hours at room temperature, stirring once every 2-4 hours during the soaking period. After soaking, filter the cake and wash it with deionized water until the pH of the filtrate is neutral. Then dry it at 70-100℃ for 8-12 hours and then transfer it to a planetary ball mill and dry ball mill at 200-300r / min for 30-60 minutes to obtain pretreated rice husk powder.

6. The method for preparing rice husk-based silicon-carbon composite material for lithium-ion battery negative electrode according to claim 5, characterized in that, S3 specifically involves mixing silicon-carbon composite material, conductive carbon black Super P, and binder LA136D at a mass ratio of 6-8:1-2:1-1.5 to obtain a mixture. Then, deionized water with a mass of 0.8-1.5 times the total mass of the mixture is added. The mixture is first pre-dispersed at a low speed of 500-800 r / min for 1-2 hours, and then stirred at a high speed of 1000-2000 r / min for 2-6 hours to prepare an electrode slurry. Electrode slurry is coated onto copper foil current collector with a coating thickness of 50-150 μm and dried at 80-120℃ for 12-24 h. After rolling and cutting, it is heat-treated in a vacuum environment at 60℃ for 2-4 h to remove residual solvent and internal stress, thus obtaining rice husk-based silicon-carbon composite material for lithium-ion battery anodes.

7. A rice husk-based silicon-carbon composite material for lithium-ion battery anodes prepared by the method according to any one of claims 1-6.